DIGITAL PROTOTYPING IN MECHANICAL ENGINEERING - NEVIMA, Jiri (Trends in education, 2010)
This article describes the realization of the project Digital Design in Mechanical Engineering at the Secondary Technical School of Mechanical Engineering in Olomouc. The project is aimed at explaining the problems of designing new engineering products to the secondary school students. Its main task is to create a new studying programme, which puts emphasis on the interdisciplinary relations and interconnects four of the subjects taught at the school. At the same time key competences of the target groups (i.e. both students and teachers) are developed, using computer technology.
Keywords: CAD; CAM; digital prototyping; digital design; computer technology; key competences; interdisciplinary relations; project writing; technical English.